Ethnic Differences in the Prevalence of Type 2 Diabetes Diagnoses in the UK: Cross-Sectional Analysis of the Health Improvement Network Primary Care Database - Pham TM (Clinical Epidemiology, 2019)
Tra My Pham,1,2 James R Carpenter,1,3 Tim P Morris,1 Manuj Sharma,2 Irene Petersen2,4 1MRC Clinical Trials Unit at UCL, London WC1V 6LJ, UK; 2Department of Primary Care and Population Health, University College London, London NW3 2PF, UK; 3Department of Medical Statistics, London School of Hygiene & Tropical Medicines, London WC1E 7HT, UK; 4Department of Clinical Epidemiology, Aarhus University, Aarhus N 8200, DenmarkCorrespondence: Tra My PhamMRC Clinical Trials Unit at UCL, 90 High Holborn, London WC1V 6LJ, UKTel +44207 670 4626Email tra.pham.09@ucl.ac.ukAims/Hypothesis: Type 2 diabetes mellitus is associated with high levels of disease burden, including increased mortality risk and significant long-term morbidity. The prevalence of diabetes differs substantially among ethnic groups. We examined the prevalence of type 2 diabetes diagnoses in the UK primary care setting.Methods: We analysed data from 404,318 individuals in The Health Improvement Network database, aged 0–99 years and permanently registered with general practices in London. The association between ethnicity and the prevalence of type 2 diabetes diagnoses in 2013 was estimated using a logistic regression model, adjusting for effect of age group, sex, and social deprivation. A multiple imputation approach utilising population-level information about ethnicity from the UK census was used for imputing missing data.Results: Compared with those of White ethnicity (5.04%, 95% CI 4.95 to 5.13), the crude percentage prevalence of type 2 diabetes was higher in the Asian (7.69%, 95% CI 7.46 to 7.92) and Black (5.58%, 95% CI 5.35 to 5.81) ethnic groups, while lower in the Mixed/Other group (3.42%, 95% CI 3.19 to 3.66). After adjusting for differences in age group, sex, and social deprivation, all minority ethnic groups were more likely to have a diagnosis of type 2 diabetes compared with the White group (OR Asian versus White 2.36, 95% CI 2.26 to 2.47; OR Black versus White 1.65, 95% CI 1.56 to 1.73; OR Mixed/Other versus White 1.17, 95% CI 1.08 to 1.27).Conclusion: The prevalence of type 2 diabetes was higher in the Asian and Black ethnic groups, compared with the White group. Accurate estimates of ethnic prevalence of type 2 diabetes based on large datasets are important for facilitating appropriate allocation of public health resources, and for allowing population-level research to be undertaken examining disease trajectories among minority ethnic groups, that might help reduce inequalities.Keywords: ethnicity, type 2 diabetes, primary care database, electronic health records, multiple imputation, missing not at random